2016
DOI: 10.13083/reveng.v24i2.664
|View full text |Cite
|
Sign up to set email alerts
|

Production and Tillering of Mombaça Grass With Different Sources and Levels of Applied Nitrogen

Abstract: Nitrogen influences numerous physiological and morphological traits of forage grasses, which ultimately interfere directly with production and forage quality. Aimed to study was to evaluate the production of dry matter and the number of tillers of Panicum maximum cv. Mombaça grown with different sources and levels of applied nitrogen. The experiment was conducted at the Federal Institute of the Espírito Santo, Campus of Santa Teresa. The experimental design consisted of a randomised block design with three rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Sulfur is essential for the synthesis of some proteins (PAIVA & NICODEMO, 1994) and, therefore, an increase in forage mass production (P<0.05) can be observed in the treatment with sulfur alone when compared to the control treatment (Table 2). Rosado et al (2016), evaluating nitrogen fertilization with three different sources (urea, ammonium sulfate and calcium nitrate), observed that Megathyrsus maximus cv. "Mombaça" obtained a response of 13.6% more in production when they used ammonium sulfate compared to the treatment that received urea.…”
Section: Resultsmentioning
confidence: 99%
“…Sulfur is essential for the synthesis of some proteins (PAIVA & NICODEMO, 1994) and, therefore, an increase in forage mass production (P<0.05) can be observed in the treatment with sulfur alone when compared to the control treatment (Table 2). Rosado et al (2016), evaluating nitrogen fertilization with three different sources (urea, ammonium sulfate and calcium nitrate), observed that Megathyrsus maximus cv. "Mombaça" obtained a response of 13.6% more in production when they used ammonium sulfate compared to the treatment that received urea.…”
Section: Resultsmentioning
confidence: 99%